FAKTOR - FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (Studi Empiris pada Perusahaan Manufaktur di BEI tahun 2011-2013) - Sianipar, Riduan Febri; Desmiyawati, Desmiyawati; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objectives of this research are to analyze auditor switching (Y), audit firm size (X1), size client company (X2), financial distress (X3), audit tenure (X4) and audit opinion (X5) against the auditor switching (empirical studies on manufacturing companies in BEI 2011-2013). The sample of this research are 42 companies in the 3-year time period from 2011 to 2013 amounted to 126 companies. Data were collected through IDX data obtained from 2011 to 2013. The sampling technique using purposive sampling method. Technique is the logistic regression analysis..The sampling technique used purposive sampling method. The analysis technique used is logistic regression analysis. Logistic regression test showed that variable of size client company, audit tenure dan audit opinion have significant effect on audit switching. Audit firm size dan financial distress has no significant effect on audit switching. While simultaneously using the Omnibus Tests of Model Coefficients five independent variables together can influence the auditor switching. The ability of independent variables to explain the profitability of 32.8%, while the remaining 67.2% are outside the model. This means that the independent variables are no t strong enough to explain his relationship with the dependent variable.Keywords : audit switching, audit firm size, size client company, financial distress and audit opinion.